(3GdOdjd GdUZjQs - (3CHh eMeO GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdQSj, GdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3SCd GdMSf Hf GdbGSe CHGg Yf GdMLI Ydi ef CfLO ai Gddg JeQOkG Ch LgdkG s
(3BNQgG (B:s
(3hGdVYa hGdTjH agh GdEafGA hGdJOejQ hUdhGJ Gddg Ydi GdHTjQ GdfPjQ Je s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs